Evaluasi Efektivitas Strategi Promosi Perguruan Tinggi Menggunakan Algoritma DBSCAN dan Sistem Informasi Geografis - Sania Darista; Rozali Toyib (TIN: Terapan Informatika Nusantara, 2026)
Campus promotions that lack a clear direction often lead to inefficient budget use and imbalanced differences in the number of applicants between regions. This study aims to examine how effective the promotional methods used by the University of Muhammadiyah Bengkulu are, using a combination of the DBSCAN algorithm and Geographic Information Systems. The DBSCAN algorithm is used to group data from prospective students based on the density of applicants and identify areas that are unusual or have irrelevant data, while GIS helps to visually map the distribution patterns of these data. The evaluation results show that applicants tend to gather in certain areas that support the success of the promotion, while also identifying potential areas that have not been optimally reached, the model evaluation produces a Silhouette Score of 0.159, which indicates spatial overlap, GIS visualization successfully provides a clear picture of the distribution of students, The contribution of this study is to integrate the DBSCAN algorithm with Geographic Information Systems to evaluate the effectiveness of promotional strategies based on the spatial distribution of prospective students so that it can provide recommendations for more targeted and data-based promotional areas. These insights provide a strategic foundation for designing more efficient, targeted, and data-driven marketing campaigns in high-potential regions.